Power Plant Synthesis - Katsaprakakis, Dimitris Al. (Boca Raton, FL : CRC Press, 2020)
Power Plant Synthesis provides an integrated approach to the operation, analysis, simulation, and dimensioning of power plants for electricity and thermal energy production. Fundamental concepts of energy and power, energy conversion, and power plant design are first presented, and integrated approaches for the operation and simulation of conventional electricity production systems are then examined. Hybrid power plants and cogeneration systems are covered, with operating algorithms, optimization, and dimensioning methods explained. The environmental impacts of energy sources are described and compared, with real-life case studies included to show the synthesis of the specific topics covered.
OCLC-licensed vendor bibliographic record.
Keywords: Electric power-plants.; SCIENCE / Energy; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Mechanical